Russian and Latvian proverbs and sayings on sin - Polytsya N. (Слово.ру: балтийский акцент, 2013)
This article examines the semantic scope of the notions of «грех / grēks» as fundamental ones in Russian and Latvian worldviews. Russian and Latvian proverbs and sayings help identify the basic, universal ideas about sin, as well as particular, national ones. The author comes to a conclusion that the Russian mentality — unlike the Latvian one — reflects the interaction and partial interference between the Christian an folk worldviews, whereas the notion of sin is found in the intersection areas, which is indicative of their similarity rather than identity.